ANALYSIS OF THE RESULTS OF COMPREHENSIVE TREATMENT OF PATIENTS WITH PANCREONECROSIS COMPLICATED WITH SEPSIS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
A retrospective cohort study of the results of a comprehensive examination and treatment of 97 patients with pancreatic necrosis was conducted. Analysis of the results of traditional methods of treating pancreatic necrosis complicated by sepsis showed a high level of disease complications of 38.1% and mortality of 30.9%, due to the lack of objective criteria for predicting the development of pancreatogenic sepsis and multiple organ dysfunction syndrome, which requires detailed studies of the pathogenetic mechanisms of this terrible disease .